INTEGRATING DEEP LEARNING APPROACHES INTO MATHEMATICS INSTRUCTION TO IMPROVE FORMULA MASTERY IN GRADE 5 - Christina Yulinda Prihasti; Stefanus Christian Relmasira (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of mathematical formula mastery among fifth-grade elementary school students due to surface learning, causing students to memorize formulas without understanding the concepts. This study aimed to analyze the effect of the Deep Learning approach through the Discovery Learning model on students’ mastery of mathematical formulas compared with the Cooperative Learning model. This study employed a quasi-experimental method using a non-equivalent control group design. The sample consisted of 38 fifth-grade students at SDN Kandangan 02 and SDN Kandangan 03. Data were collected using a hybrid test and analyzed through normality, homogeneity, and Independent Samples T-Test using IBM SPSS. The results showed that the experimental group I achieved a higher posttest mean score (73.684) than the experimental group II (58.947). The t-test result indicated a significant difference between the two groups with t = 2.657 and significance value 0.012 < 0.05. Therefore, the Deep Learning approach through the Discovery Learning model was more effective in improving students’ mastery of mathematical formulas.